Effect of intra planar differential settlement analysis of boiler supporting structure - A case study - M., Suneel Kumar; P., Jayabalan, Dr.; C., Natarajan, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/